2006
DOI: 10.2223/jped.1551
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IgE monoclonal antibody for the treatment of asthma and other manifestations related to allergic diseases

Abstract: Objectives: To report on the pharmacology, efficacy and safety of omalizumab , a new option for the treatment of asthma and allergic diseases and the first monoclonal anti-IgE antibody approved for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…The current pharmacological therapy for asthmatic patients includes inhaled short-acting b-agonists (178), long-acting bagonist (179), inhaled corticosteroids (180), systemic corticosteroids (181), leukotriene receptor antagonist (182), and biological agents, mainly monoclonal antibodies, directed against different immunological targets involved in the occurrence and severity of allergic asthma symptoms (183)(184)(185)(186). Among the biological agents currently available for asthma treatment, some of the most used are mepolizumab, reslizumab, and benralizumab, which interfere with the functions of IL-5 and, in the case of the latter, has cytotoxic activity against cells that express the IL-5 receptor; dupilumab, that blocks IL-4 receptor a (187-189); omalizumab, that leads to a reduce binding of IgE to its receptor as well as downregulates the FcϵRI expression (190); and tezepelumab, that blocks TSLP and probed useful in cases of type-2 low asthma (191).…”
Section: Reconsidering Current Treatment Of Asthmamentioning
confidence: 99%
“…The current pharmacological therapy for asthmatic patients includes inhaled short-acting b-agonists (178), long-acting bagonist (179), inhaled corticosteroids (180), systemic corticosteroids (181), leukotriene receptor antagonist (182), and biological agents, mainly monoclonal antibodies, directed against different immunological targets involved in the occurrence and severity of allergic asthma symptoms (183)(184)(185)(186). Among the biological agents currently available for asthma treatment, some of the most used are mepolizumab, reslizumab, and benralizumab, which interfere with the functions of IL-5 and, in the case of the latter, has cytotoxic activity against cells that express the IL-5 receptor; dupilumab, that blocks IL-4 receptor a (187-189); omalizumab, that leads to a reduce binding of IgE to its receptor as well as downregulates the FcϵRI expression (190); and tezepelumab, that blocks TSLP and probed useful in cases of type-2 low asthma (191).…”
Section: Reconsidering Current Treatment Of Asthmamentioning
confidence: 99%
“…Omalizumab also inhibits binding of IgE to FcεRI on dendritic cells and to FcεRII on lymphocytes T and B, eosinophils, and on other cells (Sarinho and Cruz 2006). This binding reduces the expression of receptors on the effector cells.…”
Section: Omalizumabmentioning
confidence: 99%
“…The use of monoclonal anti-IgE antibody has not been approved for the treatment of allergic rhinitis, although clinical trials have revealed its efficacy. (55,56)…”
Section: Anti-ige Antibodiesmentioning
confidence: 99%